The length of the gestation period, calving interval, and service period in indigenous West African cattle: N'Dama, West African Shorthorn and Sokoto Gudali - Sada, I. (1968)
Reproductive performance of West African cattle is investigated. Data on age of cows at first calving, length of gestation period and calving interval, and service period in N'Dama, West African Shorthorn and Sokoto Gudale cattle included.